Direct measurement of oxygen in river substrates. (4th December 2013) - Neill, Michael; Walsh, Niamh; Lucey, John
Abstract A study was conducted to establish if river substratum dissolved oxygen (DO) could be measured directly. Hitherto, such measurements have been carried out by proxy and indirect methods or by direct methods following installation of cores/tubes into the streambed. Redox potential (Eh) readings were also taken at most of the sites for comparison. The overall conclusion is that a reliable, off‐the‐shelf instrumental method of directly measuring DO in river substrates has been tested in laboratory and field conditions. The Eh meter, per contra, did give aberrant results for some measurements particularly in the field but had the advantage of a slimmer probe for easier penetration into substrata. The measurement technique, to determine river interstitial sediment O2, is a simple and quick direct in situ method that produces reliable results.